Designing dicationic organic salts and ionic liquids exhibiting high fluorescence in the solid state - David King; Matthew C. Le; Yan P. Arnaiz; Seonghyeok L. Cox; Jakob Smith; Haesook Han; Pradip K. Bhowmik (Journal of Ionic Liquids)
Dicationic ionic liquids (DILs) are emerging as a powerful, next-generation approach to designing applied ILs because of their superior physicochemical properties as well as their diverse complexity and tunability for task specific applications. DILs are scarce in the literature compared to monocationic ILs (MILs), and one of their main issues is their expected tendency to possess higher melting temperatures. A series of 1,4-bis[2-(4-pyridyl)ethenyl]benzene and 1,4-bis[2-(2-pyridyl)ethenyl]benzene quaternary salts (Q-BPEBs) with different counterions (bromide, tosylate, and triflimide) and carbon chain lengths (C6, C9, and C12) have been synthesized for their potential as DILs with strong photoluminescent properties in the solid state. All Q-BPEB salts demonstrated robust thermal stabilities as determined by thermogravimetric analysis (TGA). The differential scanning calorimetry (DSC) thermograms for Q-BPEB tosylates and triflimides displayed crystalline polymorphisms before melting transitions as verified by polarizing optical microscopy (POM). The Q-BPEB bromide and tosylate salts all showed high melting points of above >170 °C because of their dicationic rigid structures and strong ionic interactions of their anions. Once the Q-BPEB tosylates were exchanged with triflimide ions, para- isomers 1aTf2N, 1bTf2N, 1bTfand 2N,and 1cTf2N still possessed very high melting points (>225 °C), however, the ortho- isomers 2aTf2N, 2bTf2N, and 2cTf2N exhibited melting points lower than 100 °C, classifying them as DILs. Their photoluminescent properties were also studied in methanol with the emission values of λem = 476–482 nm for the para- isomers and those of λem = 448–453 nm for the ortho- isomers. In the solid state, the Q-BPEB salts exhibited strong fluorescence with quantum yields of up to 50 %. The relatively simple synthesis of these fluorescent dicationic organic salts and ILs are pertinent towards the scarcity of these materials in the literature and provide a deeper insight on the design of fluorescent ILs containing more than one charge center.